Assessment of the structural and process aspects of pharmaceutical care at a university hospital in Ethiopia - Abdrrahman Shemsu Surur; Fitsum Sebsibe Teni; Genet Girmay; Elsabet Moges; Meseret Tesfa; Messele Abraha (Wolters Kluwer Medknow Publications, 2015)
Objective: To assess the structural and process components of the pharmaceutical care at Gondar University Referral Hospital (GURH). Materials and Methods: An institution-based cross-sectional study was conducted on all the four pharmacies at GURH from October 1 to December 31, 2013. By adopting data collection instruments from a previously done study, the structural aspects of the pharmacies were assessed using an observation checklist and the process of pharmaceutical care delivery using a self-administered questionnaire. The data collected was entered to and analyzed using Statistical Packages for Social Sciences (SPSS) version 16.0. Results: none of the pharmacies had a private counseling room, fire extinguisher and meeting area. None of the pharmacy stores were equipped with fan and air ventilation system and had no cross aisles. The mean values for documentation, patient assessment and implementation of therapeutic objective were 12.14, 14.03 and 5.64 respectively. Many pharmacists (64.29%) did not participate in ward rotation with physicians. The overall pharmacy professionals' level of job satisfaction was found to be 2.77. Conclusion: There were gaps in the structure and the process of the provision of pharmaceutical care in GURH.